Benchmark dose modelling in regulatory ecotoxicology, a potential tool in pest management. Issue 5 (31st December 2021) - Jensen, Signe M.; Kluxen, Felix M.; Ritz, Christian
Abstract: For several authorities, benchmark dose (BMD) methodology has become the recommended approach by which to derive reference values for risk assessment. However, in practice, the BMD approach is not standard use in risk assessment for pesticides where the no observed adverse effect level, lowest observed adverse effect level and effective dose (ED50 or EDx ) prevail. Regression‐based BMD and the benchmark dose lower confidence limit (BMDL) have several advantages, such as utilizing more information from the generated data and being less dependent on tested dose levels. However, the BMD approach requires some degree of expert knowledge for defining an appropriate risk level for estimating the BMD and using more sophisticated statistical methods to calculate BMD and BMDL. The BMD approach is one way to move away from p value‐based binary decision‐making towards putting the weight on effect sizes. We review the advantages and disadvantages of focusing on the BMD approach for risk assessment of pesticides. Further, we discuss potential applications in efficacy trials for pest management purposes. © 2021 Society of Chemical Industry. Abstract : This article reviews the advantages and disadvantages of focusing the risk assessment of pesticides on the benchmark dose approach compared with relying on the no observed adverse effect level or an effective dose.